IMPROVING STUDENTS’ WRITING RECOUNT ACHIEVEMENT THROUGH PICTURE WORD INDUCTIVE MODEL (PWIM) - Erniwati Silitonga; Tjut Ernidawati (Universitas Negeri Medan, 2013)
Abstract This research attempts to improve students’ writing recount achievement by using Picture Word Inductive Model (PWIM). The result showed the improvement of students’ writing recount achievement. It was found that the mean of the students’ scores in every test was improved. In the first test, the mean was 53.8 and there was 8.3% of the students who got up 70 points (Minimum Completeness Criteria), in the second test, it was 68.7 and 50% of the students who got up 70 points, and in the last one, the mean was 78.4 and there was 97.2% of the students who got up 70 points. The result of the research showed the progress of achievement scores. Based on the diary note, observation sheet, questionnaire sheet and interview sheet it shows that the students felt enthusiastic, enjoyable, and active in learning recount text through Picture Word Inductive Model (PWIM). It can be concluded that Picture Word Inductive Model (PWIM) gives contribution to improve students’ writing recount achievement. Keywords: Achievement, Writing, Recount, Picture Word Inductive Model (PWIM)